A novel device to assess hip strength: Concurrent validity and normative values in male athletes. (January 2019) - O'Brien, Michael; Bourne, Matthew; Heerey, Joshua; Timmins, Ryan G.; Pizzari, Tania
Highlights: New novel device (GroinBar) correlates well with hand-held dynamometry for hip strength testing. Normative values for male Australian rules football and football (Soccer) players identified. No differences in strength found between those with and without past history of groin pain.